Improving socio-economics through rainfed bael - Singh, A. K.; Joshi, H. K.; Singh, Sanjay (Indian Horticulture, 2019)
Introduction: The bael trees grow successfully in purely rainfed conditions. Its cultivation has been very economic for small and marginal farmers, promising for ameliorating marginal degraded wastelands in semi-arid tracts of western India. All the parts of its tree have great promise with respect to malnutrition since it is nutraceutically and therapeutically very important fruit tree which is used in different forms for various purposes. Therefore, its cultivation may alleviate the economic condition of resource poor farmers, ensuring health and nutritional security of the farming community as well as consumers.